Influence of statin therapy on 24-hour blood pressure monitoring indices in patients with arterial hypertension combined with subclinical hypothyroidism - Syvolap, V. V.; Novikov, Ye. V.; Potapenko, M. S. (Zaporozhye Medical Journal, 2020)
The high prevalence of arterial hypertension (AH) and the proportion of patient category with inadequate blood pressure control, mainly leading to cardiovascular complications of hypertension, necessitate a further study of reasons for antihypertensive therapy ineffectiveness. There are data on subclinical hypothyroidism (SH) influence on systemic hemodynamics, in particular, on arterial blood pressure. However, there is a lack of information regarding the effect of concomitant SH on systemic hemodynamics and antihypertensive therapy effectiveness in AH patients. There is also an outstanding issue related to the influence of statins on 24-hour blood pressure monitoring parameters in the first-line antihypertensive drugs treatment for patients with AH and concomitant SH. The aim of this work: to study the effect of statins on the parameters of 24-hour blood pressure monitoring in patients with AH combined with SH. Materials and methods. After an informed consent was signed, 74 patients with stage II AH, grade 1–3, high and very high additional cardio-vascular risk were included in the study, of whom 43 were patients without and 31 patients with concomitant SH. Depending on the therapy assigned, the patients were divided into three groups. The first group included 22 patients with AH without concomitant SH who were prescribed only antihypertensive drugs without statin add-on therapy. The second group consisted of 21 patients with AH and without concomitant SH who were prescribed antihypertensive drugs with statin add-on therapy. The third group was composed of 31 patients with AH and concomitant SH who were prescribed antihypertensive drugs with statin add-on therapy. The groups were matched for age, gender and main anthropometric indices. Prior to treatment and after an one-year follow-up, all patients underwent 24-h blood pressure monitoring on a bifunctional device “Kardiotechnica-04” (“INCART”, St. P., the RF) with simultaneous registration of blood pressure and ECG. Statistical processing of the material was performed using the software package Statistica 13.0 (Statsoft, USA), license number JPZ8041382130ARCN10-J). The normality of quantitative signs distribution was analyzed by the Shapiro–Wilk test. Parameters with a normal distribution were presented as an arithmetic mean and standard deviation (M ± SD). For indices that had a different from normal distribution, descriptive statistics data were provided as medians and lower and upper quartiles, Me (Q25; Q75). Comparison of quantitative indices in groups was performed using Student’s and Mann–Whitney criteria, depending on the distribution character. Qualitative indices were compared using Pearson’s χ2. A difference of P < 0.05 was considered statistically significant. All tests were two-sided. Results. In 82 % (18/22) patients with AH without concomitant SH on long-term antihypertensive treatment without statin add-on therapy, the target blood pressure level as well as a significant 5.3 % (P = 0.013) decrease in the mean daytime SBP and a 7 % (P = 0.009) decrease in the mean nighttime SBP was achieved. There were no significant changes in the daily profiles of SBP and DBP, indices of hypertension and hypotension, SBP and DBP variability during the day and night. In patients with AH without concomitant SH on the long-term antihypertensive treatment with statin add-on therapy over a period of one-year, there was a significant 6.6 % (P = 0.025) decrease in the mean daytime SBP, 11.8 % (P = 0.002) in the mean nighttime SBP, 7.7% (P = 0.037) in the mean nighttime DBP, 23 % (P = 0.010) in the daytime SBP hypertension index, 34 % (P = 0.035) in the index of daytime percentage DBP increase, 21 % (P = 0.035) in the index of daytime SBP load in the absence of changes in pulse pressure indices, SBP and DBP variability during the day and night as well as daily profiles of SBP and DBP. The target level of arterial blood pressure was achieved in 86 % (18/21) of patients with AH without concomitant SH on antihypertensive treatment with statin add-on therapy. The patients with AH and concomitant SH on the long-term antihypertensive treatment with statin add-on therapy over a period of one-year demonstrated a significant decrease in the mean daytime SBP by 4.4 % (P = 0.044), mean daytime DBP by 9.8 % (P = 0.034), index of daytime percentage SBP increase by 31 % (P = 0.029), index of daytime percentage DBP increase by 27 % (P = 0.031), index of daytime SBP load by 33 % (P = 0.031) in the absence of changes in circadian rhythms of pressure, SBP and DPB variability during the day and night. As a result of the treatment, the target daytime and nighttime SBP levels were achieved in 74 % (23/31) and 65 % (20/31) of patients, respectively; the target daytime and nighttime DBP levels were achieved in 87 % (27/31) and 71 % (22/31) of patients, respectively. Conclusions. Subclinical hypothyroidism is an additional cardio-vascular risk factor that reduces the effectiveness of antihypertensive therapy, while the addition of statins to antihypertensive treatment regimens contributes to an improvement in results.